GIANT CEMENTOBLASTOMA OF LEFT MAXILLA INVOLVING A DECIDUOUS MOLAR - Javed, Anam; Shah, Syed Majid Hussain (Journal of Ayub Medical College Abbottabad, 2017)
Cementoblastoma is a relatively rare benign tumour. The clinicopathologic features, radiological findings, treatment and prognosis are reported here in a 10-year-old girl who presented to us from Afghanistan. The tumor was managed surgically and the histopathology confirmed the diagnosis of cementoblastoma. There was no evidence of recurrence at one year of follow up. Keywords: Cementoblastoma; Odontogenic tumour; Deciduous molar